Evaluation of Motorcycle Fueled with Blends of Gasoline and Pyrolytic Oil from Plastic‒Palm Kernel Shell Co-Pyrolysis - Thoharudin, Thoharudin; Santosa, Tito Hadji Agung; Iswandi, Iswandi (Departemen Teknik Mesin, Fakultas Teknik, Universitas Diponegoro, 2025)
This study explores the co-pyrolysis of plastic grocery bags and palm kernel shells (PKS) as a sustainable solution for addressing plastic waste and producing renewable energy. A stainless-steel batch reactor operating at 500oC produced pyrolytic oil, char, and non-condensable gases, with a product yield of 48.3%, 26.7%, and 25.0%, respectively. Pyrolytic oil was characterized by higher viscosity, density, and oxygen content but a lower heating value compared to gasoline (pertalite). Various blends of pyrolytic oil (0–30%) with pertalite were tested in a 108 cc motorcycle engine. While pure pertalite offered better torque and power at low speeds, pertalite with 10% and 20% pyrolytic oil showed comparable engine performance at low to medium rotational speeds and better performance at high rotational speeds. In addition, blends with higher pyrolytic oil concentrations improved fuel efficiency, with the 30% blend achieving the best fuel economy at 33.3 km/L. The study concludes that pyrolytic oil can be a viable alternative fuel for motorcycles, particularly in carburetor systems, but requires further refinement to address particulate content and enhance compatibility with fuel injection systems.